2016
DOI: 10.1021/acs.bioconjchem.5b00656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metalation on Porphyrin-Based Bifunctional Agents in Tumor Imaging and Photodynamic Therapy

Abstract: Herein we report the syntheses and comparative photophysical, electrochemical, in vitro, and in vivo biological efficacy of 3-(1'-hexyloxy)ethyl-3-devinylpyropheophorbide-cyanine dye (HPPH-CD) and the corresponding indium (In), gallium (Ga), and palladium (Pd) conjugates. The insertion of a heavy metal in the HPPH moiety makes a significant difference in FRET (Förster resonance energy transfer) and electrochemical properties, which correlates with singlet oxygen production [a key cytotoxic agent for photodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…The decay of 124 I( b + 23 %, EC 77 %) is followed by emission of an umber of high-energy g photons:6 03 keV (61 %), 723 (10 %), and 1691 (10 %), in addition to 511keV annihilation photons. The quantitative phantom studies of 124 Ii maging with different scanners [29,30] have shown that, compared with 18 Fi maging, there is only as mall loss in image resolution and contrast due to as mall increase in background from high-energy g photons from 124 I.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decay of 124 I( b + 23 %, EC 77 %) is followed by emission of an umber of high-energy g photons:6 03 keV (61 %), 723 (10 %), and 1691 (10 %), in addition to 511keV annihilation photons. The quantitative phantom studies of 124 Ii maging with different scanners [29,30] have shown that, compared with 18 Fi maging, there is only as mall loss in image resolution and contrast due to as mall increase in background from high-energy g photons from 124 I.…”
Section: Methodsmentioning
confidence: 99%
“…Ex vivo biodistribution (PET imaging and relative uptake volume (RUV)):F or the biodistribution study,t hree female BALB/c mice for [ 18 [14] and determined to be 94 mCi mmol À1 with 95 %r adiospecificity for [ 124 I]4. [ 18 F]FDG in 0.9 %s aline at 1mCi mL À1 was purchased from Cardinal Health (Rochester,N Y, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, visible light absorbance by endogenous biological fluorophores such as heme and flavin groups 6 causes autofluorescence and weak signal intensity. On the other hand, NIR light is minimally absorbed by biological material, drastically reducing background noise and increasing penetrance 7,8 . FDA-approved NIR-responsive fluorescent dyes including indocyanine green, 5-aminolevulinic acid, and methylene blue are available and used in medical diagnostics 9 , but are limited due to their low level of brightness.…”
Section: Introductionmentioning
confidence: 99%